Reliability model and critical factors identification of construction safety management based on system thinking - Zhang, Wei; Zhang, Xiao; Luo, Xiaowei; Zhao, Tingsheng (Journal of Civil Engineering and Management, 2019)
Safety is a key objective of construction management, but construction safety management is complex due to various types of technical and management factors. If critical factors can be identified and corresponding measurements can be adopted, it will be more direct and effective to improve safety performance. In this paper, by using the system thinking method, construction safety management is considered as a system and decomposed into six subsystems and related management factors. The fuzzy fault tree analysis method was used to build a reliability analysis model and reveal the failure probabilities of factors in the safety organization management subsystem. Through a questionnaire survey conducted in Wuhan, China, the pivotal importance degrees and average occurrence probabilities of basic factors are figured out. On the basis of that, nine critical factors of the safety organization management subsystem are identified and corresponding improvement measurements are proposed. More, a case study of Hangzhou underground railway tunnel collapse accident in 2008 is conducted, which verifies that the framework of construction safety management based on system thinking can be a useful tool for identifying faults or failure reasons of construction safety management.